2020
DOI: 10.1016/j.bja.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive ventilation for COVID-19-associated acute hypoxaemic respiratory failure: experience from a single centre

Abstract: Post-market modification of valves from AMBU bags (AMBU Inc, Columbia, MD, USA) may be more susceptible to failure during use compared with our use of commercial pressure regulators (produced under ISO standards). Our data do not cover the full range of clinical parameters. For our studies, inspiratory times were kept fixed, although in actual patients, inspiratory times may be intermittently adjusted. Furthermore, this scheme is not intended as a permanent solution for ventilating multiple patients, and shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 8 publications
1
49
0
4
Order By: Relevance
“…Our population consists of 96 critical COVID-19 patients with mean age 69.65 +/-14.33 years old, 28.9% of whom female, and 30.2% needed transfer to ICU, while 46.9% of the patients deceased. In our study mortality, despite being considerable, must be compared with other experiences of COVID-19 units dedicated to non-invasive ventilatory support, and mortality rates in studies that consider non-invasive ventilation treated COVID-19 patients vary from 45% of this large multicentered German study 7 to sensibly higher values (79%, 83.3%) of studies with smaller samples 8,9 . Aim of our study was to identify mortality prognostic features, possible gender-related differences and to identify ICU transfer prognostic factors.…”
Section: Discussionmentioning
confidence: 96%
“…Our population consists of 96 critical COVID-19 patients with mean age 69.65 +/-14.33 years old, 28.9% of whom female, and 30.2% needed transfer to ICU, while 46.9% of the patients deceased. In our study mortality, despite being considerable, must be compared with other experiences of COVID-19 units dedicated to non-invasive ventilatory support, and mortality rates in studies that consider non-invasive ventilation treated COVID-19 patients vary from 45% of this large multicentered German study 7 to sensibly higher values (79%, 83.3%) of studies with smaller samples 8,9 . Aim of our study was to identify mortality prognostic features, possible gender-related differences and to identify ICU transfer prognostic factors.…”
Section: Discussionmentioning
confidence: 96%
“…However, a small study on patients with influenza A on HFNC showed that 45% avoided intubation, although all of the patients with severe hypoxemia were eventually intubated ( 56 ). Some institutions are concerned that HFNC can aerosolize the virus, leading to possible exposure of health care workers, though early evidence suggests appropriate PPE is effective in mitigating this risk ( 57 , 58 , 59 ). Manikin studies suggest that the dispersal of liquid from HFNO at 60 L/min is minimal, and significantly less than that caused by coughing and sneezing, providing that nasal cannulae are well fitted ( 60 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…A small study on patients with COVID-19 in Wuhan found that 72% of patients treated with NIPPV died, and the mortality rates were similarly high for those treated with NIPPV and intubation ( 8 ). More recent studies have shown patients with moderate-to-severe COVID-19 ARDS may be managed successfully on NIPPV alone, but these remain limited to small retrospective cohorts ( 58 , 66 ). NIPPV also aerosolizes the virus, and given the unclear benefit to patients with hypoxemic respiratory failure, it should not be a first-line treatment in most circumstances ( 57 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deaths are only likely to occur if from nonrespiratory causes such as sepsis or nonrespiratory organ failure, otherwise they would have been escalated to IMV/ECMO. (10) Assume that CPAP can continue on the ward but double the mortality for reduces surrounding support etc.…”
Section: Niv/cpapmentioning
confidence: 99%
“…Observation from Sivaloganathan et al (10) Assume that CPAP can continue on the ward, but with an increase due to a reduction in other supportive care.…”
Section: Niv/cpap (Ceiling)mentioning
confidence: 99%